An Overview on the Relation Between Blood Disorders, Periodontitis and Dental Caries - Sozan Mohammed; Ahmed Zahmoul; Jbireal J M (AlQalam Journal of Medical and Applied Sciences, 2025)
The relationship between blood disorders, periodontitis, and dental caries reveals a complex interaction between oral health and systemic conditions. Dental caries, caused by bacterial biofilms and environmental factors, and periodontitis, a chronic inflammatory disease, are both associated with significant systemic implications. This review highlights the bidirectional link between these oral conditions and hematological disorders such as anemia, leukemia, and thalassemia. Periodontitis-induced inflammation can disseminate systemically, impacting hematopoietic functions and contributing to blood disorders. Conversely, hematological diseases can exacerbate periodontal issues by impairing immune responses and altering blood parameters, as observed in conditions like cyclic neutropenia and sickle cell anemia. The systemic effects of periodontitis are characterized by elevated markers, including C-reactive protein (CRP) and IL-6, amplifying chronic inflammation. This interrelationship underscores the necessity of integrative healthcare strategies. Regular monitoring of systemic markers, proactive management of periodontal inflammation, and addressing underlying hematological conditions are essential for improving patient outcomes. This review advocates for a holistic diagnostic and therapeutic approach to manage the coexisting challenges of oral and systemic health conditions effectively. تكشف العلاقة بين اضطرابات الدم والتهاب دواعم السن وتسوس الأسنان عن تفاعل معقد بين صحة الفم والحالات الجهازية. يرتبط تسوس الأسنان الناجم عن الأغشية الحيوية البكتيرية والعوامل البيئية والتهاب دواعم السن، وهو مرض التهابي مزمن، بعواقب جهازية كبيرة. تسلط هذه المراجعة الضوء على الارتباط الثنائي الاتجاه بين هذه الحالات الفموية والاضطرابات الدموية مثل فقر الدم وسرطان الدم والثلاسيميا. يمكن أن ينتشر الالتهاب الناجم عن التهاب دواعم السن على نطاق واسع، مما يؤثر على وظائف الدم ويساهم في اضطرابات الدم. وعلى العكس من ذلك، يمكن أن تؤدي الأمراض الدموية إلى تفاقم مشاكل اللثة عن طريق إضعاف الاستجابات المناعية وتغيير معايير الدم، كما هو الحال في حالات مثل نقص العدلات الدورية وفقر الدم المنجلي. تتميز التأثيرات الجهازية لالتهاب دواعم السن بعلامات مرتفعة، بما في ذلك البروتين التفاعلي سي وIL-6، مما يؤدي إلى تضخيم الالتهاب المزمن. تؤكد هذه العلاقة المتبادلة على ضرورة استراتيجيات الرعاية الصحية المتكاملة. إن المراقبة المنتظمة للعلامات الجهازية، والإدارة الاستباقية لالتهاب اللثة، ومعالجة الحالات الدموية الكامنة، كلها أمور ضرورية لتحسين نتائج المرضى. وتدعو هذه المراجعة إلى اتباع نهج تشخيصي وعلاجي شامل لإدارة التحديات المتزامنة للحالات الصحية الفموية والجهازية بشكل فعال